Effects of Grains Size and Sandblasting Duration to the Surface Hardness of the Casting Product of Used Propeller - Ahmadi, Nurfi (Sekolah Tinggi Teknologi Adisutjipto, 2018)
This research carried out the sandblasting process on used aluminum propeller castings with variations in sand grains: 40 mesh, 60 mesh, and 80 mesh with variations of 30 seconds, 60 seconds and 90 seconds. The size of the grain and the varying time result in different surface hardness. The biggest hardness on sandblasting with a grain size of 40 mesh time of 90 seconds is 39.8 VHN, 60 mesh time of 30 seconds is 38.6 VHN, 80 mesh time of 30 seconds is 37.1 VHN, from the photo macro the abrasion of the largest surface material occurs at grain size 40 mesh.